Mapeamento e análise integrada das unidades de paisagem (geofácies) do Seridó Potiguar - Medeiros, Diogo Bernardino Santos de (2019)
The chain of natural and anthropic events impressed a disparate landscape within the Brazilian Semiarid: the Seridó Potiguar. The region is detached from its surroundings by the physicalnatural and socio-cultural particularities that manifest themselves three-dimensionally inseparable on its surface. Furthermore, what seems to us to be uniform/homogeneous, when the observations and scale of approach are sharpened, moves like a true complex paisagistic mosaic, whose structure and dynamics, considering each component geofacies, faithfully reflects the details of this land and people. Mapping these landscape units (geofacies) and performing an integrated multiscale analysis (from climate zone to physiognomic facies) of their socioenvironmental dynamics established the purpose of this work. But before that, it was necessary to know deeply the geographical epistemology capable to provide the appropriate optics for this. The geosystemic theory, by the French geographer Georges Bertrand, served us precisely as this theoretical-methodological prism, which allowed us to perceive/analyze the landscape systemically, mainly from geofacies (abstraction), a physiognomically homogeneous sector on the surface, according to its taxonomic system. The categories of analysis “Temporal and Spatial Landscape Dynamics”, “Ecodynamic Landscape Typology” and “Landscape Cartography”, advocated in such theoretical and methodological conception, were taken for this study with the necessary reputed adaptations, based on works which have already endeavored to discuss and apply them. The techniques and procedures involved in this research refer mainly to cartographic modeling in a virtual environment of Geographic Information Systems. In sum, starting from previous cartographic contributions for superior higher taxa in Rio Grande do Norte (domain, natural region, geocomplex), we performed the manual vectorization, by photointerpretation/teledetection, of landscape breaks, in the scale 1:50.000, in Sentinel-2 orbital images with spatial resolution of 10 meters and real color composition R04G03B02. This was due to the construction of inductive interpretation files, which allowed, from the determination of a few cases (geofacies) and their validation in the field (with the help of the field files), to assign a generalization to compartments of the same physiognomy. The obtained data allowed to elaborate a cartographic model that pointed to the existence of 30 different geofacies in Seridó Potiguar, which had their dynamics and distinctively landscape elements synthesized (systemic analysis), in text, based on the articulation of empirical data and thematic literature. Finally, the results were qualitatively and qualitatively evaluated, in terms of spatial, absolute and relative extent, so that it was possible to undertake complements and greater robustness to the hypotheses of physiognomy and physiology of the seridoense landscapes, establishing a certain panoramic diagnosis of spatial and temporal situation and ecodynamics of these units. Thus, it is considered that the employed methodology allowed to advance in the geosystemic knowledge of the seridoense landscape, regarding to previous works, whereas these contributions are expected to minimally achieve the ultimate goal of making, through the virtuous pathways of science, country life gradually more congruent with its surroundings, especially in the seridoense hinterland.